RELATIONSHIP BETWEEN THE ROLES OF HEALTHCARE WORKERS AND ACCESS TO HEALTH CARE IN THE USE OF LONG-ACTING CONTRACEPTIVES - Cici Arlita; maryani, Deni; Neng Kurniati; Kurnia Dewiani; Damayanti (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background the main demographic issue in Indonesia is high population growth. In order to curb the population growth rate, the government implements various development programs, one of which is Family Planning. Long-Acting Contraceptive Methods are part of the government’s efforts to curb population growth. Couples of Reproductive Age can choose a contraceptive method that suits their circumstances and needs based on information they have understood, including the advantages, disadvantages, and factors that influence contraceptive methods.Objective of this study was to determine the relationship between the role of health workers and health facilities and the selection of LCMs in the service area of the Muara Bangkahulu Community Health Center in Bengkulu City. Methods:the research used was a quantitative study with a descriptive-analytical approach employing a cross-sectional design. The sample size for this study was 96 participants, selected using accidental sampling. Analysis was performed using the chi-square test. Results: the showed that 23 respondents (23.0%) in the Muara Bangkahulu Community Health Center’s service area used Long-Acting Contraceptive Methods, support from health workers (p-value 0.000) was significantly associated with the choice of Long-Acting Contraceptive Methods (p-value < 0.05), and access to health facilities (p-value 0.590) was not associated with the choice of long-acting contraception (p-value > 0.05). Conclusions: Support from family planning service providers influences the decision regarding the level of participation in the LCM and Access to health care refers to the opportunities or ease with which people can obtain services according to their needs.